On the Sacred - Lynch, Gordon, 1968- (Heretics (Durham, England), 2014)
Progressive, modern societies hold the promise of the triumph of reason and the banishing of primitive, religious impulses to a bygone age. If this statement is orthodoxy to much of Western liberal thought, then Gordon Lynch''s On the Sacred is heresy. Challenging the myth of the idealized rational society, Lynch argues that emotionally-charged forms of the sacred remain an inevitable foundation of social life. Modernity has not rid us of the sacred, but merely presented us with new sacred forms focused around humanity, nature and the nation. Drawing on examples from the changing status of the.